2023
DOI: 10.1101/2023.03.29.534766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SERPINB3 induces the basal-like/squamous subtype and enhances disease progression in pancreatic cancer

Abstract: Pancreatic cancer is a heterogeneous disease with distinct subtypes. Here, we investigated candidate driver genes of the highly aggressive basal-like/squamous molecular subtype of pancreatic ductal adenocarcinoma (PDAC). Integrative transcriptomic analyses identified the upregulated serine/cysteine protease inhibitor, SERPINB3 (squamous cell carcinoma antigen 1, SCCA1) in basal-like/squamous PDAC using discovery and validation approaches. Upregulation of SERPINB3 associated with decreased patient survival and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Applying pathway enrichment analysis using MetaboAnalyst 5.0, we found that LMO3-overexpressing Panc 10.05 cells exhibited heightened lipogenesis and diminished amino acid metabolism (Figure 4E and 4F). Our findings align with previous research from our group, which showed that the basal-like/squamous subtype promotes amino acid metabolism whereas classical/progenitor tumors favor increased lipogenesis 17,23 . Notably, we observed analogous metabolic adaptation patterns in basal-like/squamous PDAC and LMO3-low PDAC cells, potentially contributing to disease progression.…”
Section: Upregulation Of Lipid Metabolism and Downregulation Of Amino...supporting
confidence: 93%
See 4 more Smart Citations
“…Applying pathway enrichment analysis using MetaboAnalyst 5.0, we found that LMO3-overexpressing Panc 10.05 cells exhibited heightened lipogenesis and diminished amino acid metabolism (Figure 4E and 4F). Our findings align with previous research from our group, which showed that the basal-like/squamous subtype promotes amino acid metabolism whereas classical/progenitor tumors favor increased lipogenesis 17,23 . Notably, we observed analogous metabolic adaptation patterns in basal-like/squamous PDAC and LMO3-low PDAC cells, potentially contributing to disease progression.…”
Section: Upregulation Of Lipid Metabolism and Downregulation Of Amino...supporting
confidence: 93%
“…Comparative analysis between the basal-like/squamous and classical/progenitor subtypes was performed using Partek Genomics Suite 7.0 (Partek Inc., Chesterfield, MO). For the integrated transcriptomic and metabolomic investigations, we utilized RNA sequencing data from patient PDAC tumors within the NCI-UMD-German cohort (GSE224564) 17 .…”
Section: Pdac Cohortsmentioning
confidence: 99%
See 3 more Smart Citations